Collateral status reperfusion and outcomes after endovascular therapy: insight from the Endovascular Treatment in Ischemic Stroke (ETIS) Registry. (17th June 2021) - Anadani, Mohammad; Finitsis, Stephanos; Clarençon, Frédéric; Richard, Sébastien; Marnat, Gaultier; Bourcier, Romain; Sibon, Igor; Dargazanli, Cyril; Arquizan, Caroline; Blanc, Raphael; Lapergue, Bertrand; Consoli, Arturo; et al.
Abstract : Background: Studies have suggested that collateral status modifies the effect of successful reperfusion on functional outcome after endovascular therapy (EVT). We aimed to assess the association between collateral status and EVT outcomes and to investigate whether collateral status modified the effect of successful reperfusion on EVT outcomes. Methods: We used data from the ongoing, prospective, multicenter Endovascular Treatment in Ischemic Stroke (ETIS) Registry. Collaterals were graded according to the American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology (ASITN/SIR) guidelines. Patients were divided into two groups based on angiographic collateral status: poor (grade 0–2) versus good (grade 3–4) collaterals. Results: Among 2020 patients included in the study, 959 (47%) had good collaterals. Good collaterals were associated with favorable outcome (90-day modified Rankin Scale (mRS) 0–2) (OR 1.5, 95% CI 1.19 to 1.88). Probability of good outcome decreased with increased time from onset to reperfusion in both good and poor collateral groups. Successful reperfusion was associated with higher odds of favorable outcome in good collaterals (OR 6.01, 95% CI 3.27 to 11.04) and poor collaterals (OR 5.65, 95% CI 3.32 to 9.63) with no significant interaction. Similarly, successful reperfusion was associated with higher odds of excellent outcome (90-day mRS 0–1) and lower odds of mortality in both groups with no significant interaction. The benefit of successful reperfusion decreased with time from onset in both groups, but the curve was steeper in the poor collateral group. Conclusions: Collateral status predicted functional outcome after EVT. However, collateral status on the pretreatment angiogram did not decrease the clinical benefit of successful reperfusion.